Crop Insurance: Security for Farmers and Agricultural Stakeholders in the Face of Seasonal Climate Variability - Sonny N. Domingo; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2009)
Crop insurance is a risk management tool designed to even out agricultural risks and address the consequences of natural disasters to make losses more bearable, especially to the marginalized farmers. In the Philippines, the Philippine Crop Insurance Corporation (PCIC) implements and manages the government program on agricultural insurance. This paper provides a comprehensive review of the crop insurance program in the Philippines - its history, operationalization, performance, and a number of challenges. Some of the identified constraints in operating the program are high overhead cost, need for larger investment fund, and question of sustainability. The results of secondary data assessment and key informant interviews revealed that PCIC has captured only a small segment of its target clientele, particularly the subsistence farmers, due to logistical and marketing constraints. Moreover, farmer dependence on informal credit, particularly in rural farming communities, seems to have also created a nonviable setting for a crop insurance program.
Keywords: 330; seasonal climate forecast (SCF); agricultural credit; crop insurance; Philippine Crop Insurance Corporation (PCIC); Weizenanbau; Agrarversicherung; Katastrophe; Agrarkredit; Philippinen